Who is in the emergency room matters when we talk about door-to-needle time: a single-center experience - Brunser, Alejandro M.; Nuñez, Juan-Cristobal; Mansilla, Eloy; Cavada, Gabriel; Olavarría, Verónica; Muñoz Venturelli, Paula; Lavados, Pablo M. (Arquivos de Neuro-Psiquiatria, 2023)
Background The efficacy of intravenous thrombolysis (IVT) is time-dependent.Objective To compare the door-to-needle (DTN) time of stroke neurologists (SNs) versus non-stroke neurologists (NSNs) and emergency room physicians (EPs). Additionally, we aimed to determine elements associated with DTN ≤ 20 minutes.Methods Prospective study of patients with IVT treated at Clínica Alemana between June 2016 and September 2021.Results A total of 301 patients underwent treatment for IVT. The mean DTN time was 43.3 ± 23.6 minutes. One hundred seventy-three (57.4%) patients were evaluated by SNs, 122 (40.5%) by NSNs, and 6 (2.1%) by EPs. The mean DTN times were 40.8 ± 23, 46 ± 24.7, and 58 ± 22.5 minutes, respectively. Door-to-needle time ≤ 20 minutes occurred more frequently when patients were treated by SNs compared to NSNs and EPs: 15%, 4%, and 0%, respectively (odds ratio [OR]: 4.3, 95% confidence interval [95%CI]: 1.66–11.5, p = 0.004). In univariate analysis DTN time ≤ 20 minutes was associated with treatment by a SN (p = 0.002), coronavirus disease 2019 pandemic period (p = 0.21), time to emergency room (ER) (p = 0.21), presence of diabetes (p = 0.142), hypercholesterolemia (p = 0.007), atrial fibrillation (p < 0.09), score on the National Institutes of Health Stroke Scale (NIHSS) (p = 0.001), lower systolic (p = 0.143) and diastolic (p = 0.21) blood pressures, the Alberta Stroke Program Early CT Score (ASPECTS; p = 0.09), vessel occlusion (p = 0.05), use of tenecteplase (p = 0.18), thrombectomy (p = 0.13), and years of experience of the physician (p < 0.001). After multivariate analysis, being treated by a SN (OR: 3.95; 95%CI: 1.44–10.8; p = 0.007), NIHSS (OR: 1.07; 95%CI: 1.02–1.12; p < 0.002) and lower systolic blood pressure (OR: 0.98; 95%CI: 0.96–0.99; p < 0.003) remained significant.Conclusion Treatment by a SN resulted in a higher probability of treating the patient in a DTN time within 20 minutes.
Keywords: Stroke; Fibrin Clot Lysis Time; Thrombolytic Therapy